Misconceptions and Knowledge Gaps on Antibiotic Use and Resistance in Four Healthcare Settings and Five European Countries—A Modified Delphi Study - Athina Chalkidou; Maarten Lambert; Gloria Cordoba; Katja Taxis; Malene Plejdrup Hansen; Lars Bjerrum (Antibiotics, 2023)
Misconceptions and knowledge gaps about antibiotics contribute to inappropriate antibiotic use and antimicrobial resistance. This study aimed to identify and prioritize misconceptions and knowledge gaps about antibiotic use from a healthcare professionals’ perspective. A modified Delphi study with a predefined list of statements, two questionnaire rounds, and an expert meeting was conducted. The statements were rated by healthcare professionals from France, Greece, Lithuania, Poland, and Spain, and from general practice, out-of-hour services, nursing homes, and pharmacies. A total of 44 pre-defined statements covered the following themes: (1) antimicrobial resistance in general, (2) use of antibiotics in general, (3) use of antibiotics for respiratory tract infections, and (4) use of antibiotics for urinary tract infections. Consensus was defined as ≥80% agreement between the professionals during the second Delphi round. For 30% of the statements, professionals from the four settings together reached consensus. In each setting individually, at least 50% of the statements reached consensus, indicating that there are still many misconceptions and knowledge gaps that need to be addressed. Six educational tools (leaflets, posters, checklists) were developed to address the knowledge gaps and misconceptions. These can be used by patients and healthcare professionals to improve the use of antibiotics in practice.